AN ANALYSIS OF INTRUCTIONAL MEDIA USED IN SMKN 1 KUOK (A QUALITATIF RESEARCH at SMKN 1 KUOK) - Dwi Riva Aini Fitri; Lusi Marleni; Wida Rianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to analyze the types of instructional media used by English teachers at SMKN 1 Kuok, to evaluate their effectiveness, and to identify the challenges teachers face in implementing them. The study used a qualitative descriptive method, with data collected through questionnaires and interviews involving all three English teachers at SMKN 1 Kuok. The results show that 100% of teachers use digital media such as YouTube videos, PowerPoint presentations, Kahoot, Quizizz, and Google Classroom, 100% still use printed media like textbooks and student worksheets, and 67% create their own media, including vocabulary cards and classroom games. In terms of effectiveness, 95% of teachers stated that digital media increases student motivation, 90% agreed that visual media makes learning easier to understand, and 85% noted that media enhances class interaction and engagement. However, only 33% of teachers considered school facilities adequate, and 100% mentioned obstacles such as limited projectors, weak internet connections, and lack of time to prepare new materials. Despite these challenges, the use of instructional media has significantly improved student participation and comprehension in English learning. The study concludes that effective media integration, supported by sufficient infrastructure and continuous teacher training, can greatly enhance teaching quality in vocational schools.